Strategic Maritime Diplomacy and Sovereignty: Evaluating Turkey’s Use of the Montreux Convention from an Islamic Perspective - Ahmed, Sundus Serhan (al-'adalah, 2025)
This article analyzes the strategic significance of the Montreux Convention in the framework of Turkey's foreign policy while examining the country's maritime diplomacy from the perspective of the Islamic paradigm. The Montreux Convention, established in 1936, has given Turkey considerable geopolitical influence and an important diplomatic role in the regional and global arenas. Through a qualitative approach based on historical documentation, diplomatic records, and member-state interviews, this study examines how Turkey exercises its strategic autonomy in facing complex global challenges, promoting regional stability, and strengthening national sovereignty while making strategic and opportunistic adjustments during geopolitical changes in the worldwide order. This study shows that Turkey has consistently used the Montreux Convention to support its active role as a diplomatic intermediary between major powers in an effort to create stable, friendly relations and sustainable diplomatic continuity. The country has acted as a mediator in regional armed rivalries, especially during dynamic historical periods such as the Cold War and tensions in the Black Sea. This study concludes that the Montreux Convention has ultimately established Turkey's position as a strategic player under the auspices of the rule of law and international diplomacy to maintain security and peace in the region and the global world. The policies that have been implemented are also in line with Islamic principles, which emphasize the principles of sovereignty, neutrality, peace, and cooperation